PENGARUH EFEKTIVITAS FUNGSI AUDIT INTERNAL TERHADAP PENGUNGKAPAN KELEMAHAN PENGENDALIAN INTERNAL - Dewi Yuniarti Rozali, Rozmita; Alfian, Rizal (Program Studi Akuntansi FPEB UPI, 2014)
This research purpose to know how influence the effectiveness of the internal audit function on the disclosure weaknesses control in BUMN headoffice in Bandung. The research method used is associative method. The population this research are internal auditors who are in all BUMN headoffice in Bandung, whereas for sampling using sample iteration. This research using primary data wich collected from questionnaires. This research using a simple statictical correlation Spearman Rank in analyzing the data. Based on the calculation of correlation analysis with the help of software SPSS 20.0 for Windows, questionnaire distributed to 55 internal auditors at 5 BUMN headoffice in Bandung showed that the effectiveness of the internal audit function has positive influence on the disclosure of internal control weaknesses. Percentage influence the effectiveness of the internal audit function to the disclosure of internal control weaknesses were 33.5% and 66.5% influenced by other factors not examined in this research.